Effect of different stocking densities on growth, oxidative stress, antioxidant enzymes, and hematological and immunological values of European catfish (Silurus glanis L., 1758) - Koprucu, K.; Yonar, S. Mise; Koprucu, S.; Yonar, Me (Springer, 2024)
In this study, effect of different stocking densities on growth, oxidative stress, antioxidant enzymes, and hematological and immunological values in European catfish (Silurus glanis) was examined. The control (0.06 kg fish/L) and trial (T) 1 (0.08 kg fish/L), T2 (0.10 kg fish/L), and T3 (0.12 kg fish/L) stocking groups were used. Each stocking group with three replicates was carried out in a tank at 22 +/- 2 degrees C water temperature. The fish were fed three times daily for 60 days. The highest final weight (123.3-171.6 g), weight gain (84.13-159.6%), specific growth rate (1.40-2.66%), feed intake (138.5-178.2 g/fish), and feed conversion rate (1.12-1.65%) were provided from the control and T1 stockfish (p > 0.05), followed by the T2 and T3 stockfish (p < 0.05), respectively. The lowest oxidant level and the highest reduced glutathione level and superoxide dismutase, catalase, and glutathione peroxidase activities were obtained from the control fish, followed by the T1, T2, and T3 stockfish, respectively (p < 0.05). In addition, parallel to the increase in stocking density, the erythrocyte count, hematocrit, hemoglobin, erythrocyte volume, corpuscular hemoglobin, and corpuscular hemoglobin concentration values of fish increased (p < 0.05), but the leukocyte count, nitroblue tetrazolium activity, total protein, and immunoglobulin-M values decreased (p < 0.05). The high stocking densities caused oxidative stress in fish, negatively affecting their health and growth and feed evaluation values. However, the stocking density could increase to 0.08 kg/L from 0.06 kg/L in the European catfish fingerling reared in the recirculating aquaculture system by maintaining the water quality and applying good care and feeding.
Keywords: Catfish; Hematology; Immunity; Stress; Stocking density